Analysis of Congenital Hypothyroid Screening Program on Independent Midwifery Practices - Desy Eka Soekmasari; Rini Kundaryanti; Andi Julia Rifiana (GLOBAL HEALTH SCIENCE GROUP, 2025)
Congenital Hypothyroidism Skrining (CHS) is a national program aimed at the early detection of thyroid dysfunction in newborns to prevent growth and developmental delays. Permenkes (2014) In Tangerang City, the program coverage remains far below the national target, highlighting the need to examine the factors influencing its implementation (Kemenkes RI, 2023). This study aims to analyze the relationship between individual and systemic factors and the success of CHS, while also exploring the experiences of midwives in carrying out the program. This research employed a mixed methods design with an explanatory sequential approach. The qualitative phase was carried out through in-depth interviews with selected informants to gain a more comprehensive understanding of the dynamics of program implementation, inamely the Health Office, Community Health Centers, BPM, and mothers of infants who underwent SHK in Tangerang City. Analysts used the NVivo application.The quantitative phase was followed by distributing questionnaires. The sample was taken using a purposive sampling method (inclusion and exclusion), resulting in 144 PMBs. Data analysis used descriptive and inferential statistics (chi-square test or logistic regression) using SPSS. Quantitative findings indicated that factors such as education, training, knowledge, attitudes, referral compliance, availability of equipment, reporting practices, and family support were not statistically associated with program success. However, socialization efforts showed a tendency toward stronger influence, though not yet statistically significant. Meanwhile, the qualitative phase generated six main themes reflecting the participants’ perspectives and experiences, namely understanding of CHS, implementation processes, patient responses, strategies for socialization and education, challenges in implementation, and evaluation with expectations for improvement. The success of CHS is influenced by complex factors beyond individual midwife characteristics. Strengthening socialization strategies, enhancing cross-sector collaboration, and improving coordination among stakeholders are essential to expand coverage and improve program effectiveness.